The role of EIA in influencing coastal access in two golf estates in the southern Cape coast, South Africa - Kirkby, Kenneth (Department of Environmental and Geographical Science, 2015)
As coastal development pressures continue to transform coastal regions into private havens for the benefit of a privileged few, conflicts over coastal access issues continue to increase. The southern Cape coast of South Africa is no exception to this phenomenon and the privatization of this coastal region is taking place at a rapid rate. Associated with this trend is the notable increase in large-scale golf estates developed along this coastline. Due to their size, their close proximity to the coast and their exclusive nature, loss of public access to the coast has been identified as a negative impact of such developments. The aim of this research is therefore to enhance understanding of changing coastal access patterns associated with two coastal golf estate developments along the southern Cape coast of South Africa and in particular to review and analyse the role that the Environmental Impact Assessment (EIA) processes played in influencing such access patterns.